UNRAVELING INVASIVE BREAST CARCINOMA OF NO SPECIAL TYPE WITH NEUROENDOCRINE DIFFERENTIATION : A CASE REPORT - WIJAYANTI, ARINI RIZKY (JURNAL ILMIAH SIMANTEK, 2023)
Neuroendocrine differentiation in breast cancer has been recognised since 1963 but is hindered by frequently changing terminology and diagnostic criteria. Breast carcinoma of no special type with neuroendocrine differentiation (IBC-NST-NE) is diagnosed by identifying the presence and extent of NE features. This case report emphasises the significance of establishing the IBC-NST-NE diagnosis. A 75-year-old woman presented with a year-old left breast lump, rapidly enlarging over 3 months with multiple ulcerations and bloody nipple discharge. A needle biopsy confirmed ductal carcinoma. Radical mastectomy revealed a 7,5x7,3x4,9 cm, gray-white, lobulated mass with indistinct borders. Histopathology identified invasive ductal carcinoma with 30% exhibiting NE features—arranged in an insular and pseudorosette pattern, composed of polygonal cells with granular cytoplasm and salt-and-pepper chromatin. Synaptophysin and chromogranin A were positive in the neuroendocrine component, leading to the IBC-NST-NE diagnosis. Therapy of IBC-NST-NE follows standard IBC protocol; however, it has shorter disease-free survival, a poorer survival rate, higher distant metastasis rates, and a higher TNM stage at diagnosis. Diagnosing IBC-NST-NE is crucial for prognosis and enhances our understanding of neuroendocrine differentiation behaviour in breast cancer.